Cost-effectiveness of cholesterol-lowering therapy with pravastatin in patients with previous acute coronary syndromes aged 65 to 74 years compared with younger patients: results from the LIPID study. - Tonkin, A; Eckermann, S; White, H; Friedlander, D; Glasziou, P; Magnus, P; Kirby, A; Mulray, S; Denton, M; Sallaberger, M; Hunt, D; Simes, J (2006)
BACKGROUND: We compared cost-effectiveness of pravastatin in a placebo-controlled trial in 5500 younger (31-64 years) and 3514 older patients (65-74 years) with previous acute coronary syndromes. METHODS: Hospitalizations and long-term medication within the 6 years of the trial were estimated in all patients . Drug dosage, nursing home, and ambulatory care costs were estimated from substudies. Incremental costs per life saved of pravastatin relative to placebo were estimated from treatment effects and resource use. RESULTS: Over 6 years, pravastatin reduced all-cause mortality by 4.3% in the older patients and by 2.3% in the younger patients. Older patients assigned pravastatin had marginally lower cost of pravastatin and other medication over 6 years (A dollar 4442 vs A dollar 4637), but greater cost offsets (A dollar 2061 vs A dollar 897) from lower rates of hospitalizations. The incremental cost per life saved with pravastatin was A dollar 55500 in the old and A dollar 167200 in the young. Assuming no treatment effect beyond the study period, the life expectancy to age 82 years of additional survivors was 9.1 years in the older and 17.3 years in the younger. Estimated additional life-years saved from pravastatin therapy were 0.39 years for older and 0.40 years for younger patients. Incremental costs per life-year saved were A dollar 7581 in the older and A dollar 14944 in the younger, if discounted at 5% per annum. CONCLUSIONS: Pravastatin therapy was more cost-effective among older than younger patients, because of their higher baseline risk and greater cost offsets, despite their shorter life expectancy.